The validity and reliability evaluation of the Turkish version of the perceptions of threats from emotion questionnaire (PTEQ) - Ekici Esengül; Ozdel Kadir (Psihologija, 2025)
The Perceptions of Threats from Emotion Questionnaire (PTEQ) assesses beliefs about threats related to seven basic emotions and ‘strong emotions in general’ that may contribute to understanding psychopathologies based on psychological disorders. The aim of this study was to translate and evaluate the psychometric properties of the Turkish version of the four subscales of the PTEQ (anxiety, anger, disgust, guilt). One hundred fourteen patients with clinical obsessive-compulsive disorder (OCD) and one hundred forty individuals from the general population (GP) were recruited. Confirmatory factor analyses and internal reliability analyses were conducted, and the divergent and discriminant validity of the PTEQ was examined with the Beck Depression Inventory, Beck Anxiety Inventory, and Obsessive Beliefs Questionnaire-Perfectionism/Intolerance of Uncertainty. The findings revealed that the four models for the PTEQ subscales showed an acceptable and good fit in the factor analysis and had satisfactory internal consistency (all ≥ .70) and test–retest reliability in the clinical OCD and GP samples. The 6-item subscale obtained by removing the 7th item from the PTEQ-guilt subscale is appropriate for OCD and GP samples in Turkish culture. The results support the divergent and discriminant validity of four subscales of the PTEQ in GP and OCD samples. The suggested Turkish versions of the four subscales of the PTEQ showed adequate reliability and validity, but further investigations are needed in different populations with larger samples.